Return to Work After Coronavirus Disease 2019 Acute Respiratory Distress Syndrome and Intensive Care Admission: Prospective, Case Series at 6 Months From Hospital Discharge*. Issue 11 (28th May 2021) - Carenzo, Luca; Dalla Corte, Francesca; Haines, Ryan W.; Palandri, Chiara; Milani, Angelo; Aghemo, Alessio; Pini, Daniela; Protti, Alessandro; Cecconi, Maurizio
Abstract : OBJECTIVES: Joblessness is common in survivors from critical care. Our aim was to describe rates of return to work versus unemployment following coronavirus disease 2019 acute respiratory distress syndrome requiring intensive care admission. DESIGN: Single-center, prospective case series. SETTING: Critical Care Follow-Up Clinic, Humanitas Clinical and Research Center—IRCCS, Rozzano, Italy. PATIENTS: One hundred and one consecutive laboratory-confirmed coronavirus disease 2019 patients were discharged from our hospital following an ICU stay between March 1, 2020, and June 30, 2020. Twenty-five died in the ICU. Seventy-six were discharged alive from hospital. Two patients refused participation, while three were unreachable. The remaining 71 were alive at 6 months and interviewed. INTERVENTIONS: Baseline and outcome healthcare data were extracted from the electronic patient records. Employment data were collected using a previously published structured interview instrument that included current and previous employment status, hours worked per week, and timing of return to work. Health-related quality of life status was assessed using the Italian EQ-5D-5L questionnaire. MEASUREMENTS AND MAIN RESULTS: Of the 71 interviewed patients, 45 (63%) were employed prior to coronavirus disease 2019, of which 40 (89%) of them worked full-time. Thirty-three (73%) of the previously employed survivors had returned to work by 6 months, 10 (22%) were unemployed, and 2 (5%) were newly retired. Among those who returned to work, 20 (85%) of them reported reduced effectiveness at work. Those who did not return to work were either still on sick leave or lost their job as a consequence of coronavirus disease 2019. Reported quality of life of survivors not returning to work was worse than of those returning to work. CONCLUSIONS: The majority of coronavirus disease 2019 survivors following ICU in our cohort had returned to work by 6 months of follow-up. However, most of them reported reduced work effectiveness. Prolonged sick leave and unemployment were common findings in those not returning.